2019 IEEE 89th Vehicular Technology Conference (VTC2019-Spring) 2019
DOI: 10.1109/vtcspring.2019.8746609
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Multi-Antenna Receivers for Vehicular Communications in Live LTE Networks

Abstract: Cellular Vehicle to Everything (C-V2X) communications with its safety and infotainment services will require a high performance receivers to cope with challenging throughput, latency and reliability requirements. With increasing levels of interference due to cell densification and introduction of the roadside units, single antenna receivers may not be able to provide the required quality of service. In this work we experimentally study the performance of multi antenna receivers based on more than 150 km of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…First, for validating the performance of multi-antenna receivers: beamforming and MRC are studied in [29]. The study focuses on the downlink interference observed by a vehicle and its impact on beamforming and MRC performance.…”
Section: A Conducted Measurement Campaignsmentioning
confidence: 99%
“…First, for validating the performance of multi-antenna receivers: beamforming and MRC are studied in [29]. The study focuses on the downlink interference observed by a vehicle and its impact on beamforming and MRC performance.…”
Section: A Conducted Measurement Campaignsmentioning
confidence: 99%
“…The driven roads comprise a total of more than 150 km and the speed of the vehicle varied from 0 km/h in urbanized areas up to 100 km/h in the highway. Readers can refer to [8] for further details on the driven routes. The LTE connectivity was provided by a Danish network operator whose BSs locations were known.…”
Section: A Measurement Campaignmentioning
confidence: 99%
“…Alternative solutions applied from the vehicle side become attractive for car vendors due to their possible implementation without standardization. In [8], authors have shown the potential DL Signal to Interference and Noise Ratio (SINR) gains of using receive beamforming on the vehicle side. However, receive beamforming requires expensive and synchronized hardware equipment in addition to high computational complexity of AoA estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Another proposal introduced in [5] attempts to predict Doppler changes to allow for easier compensation of the channel effects, the results outperform a benchmark least squares estimation however only simulation results are presented thus its ability to perform under real world constraints are unknown. Further proposals include the use of multiple input multiple output (MIMO) systems [6], cooperative communication [7], and integration into existing long term evolution (LTE) and future 5G systems [8]. There have also been several proposals to use machine learning in the vehicular network, such as in [9] where they investigate the use of artificial neural networks (ANNs) to increase throughput in a vehicular ad-hoc network (VANET) by optimising the medium access control (MAC) layer of the 802.11p protocol.…”
Section: Introductionmentioning
confidence: 99%